Effects of receptor modification and temperature on dynamics of sensory complexes in Escherichia colichemotaxis - Schulmeister, Sonja Elke; Große, Karin; Sourjik, Victor (BMC microbiology, 2011)
Extracellular stimuli in chemotaxis of Escherichia coli and other bacteria are processed by large clusters of sensory complexes. The stable core of these clusters is formed by transmembrane receptors, a kinase CheA, and an adaptor CheW, whereas adaptation enzymes CheR and CheB dynamically associate with the clusters via interactions with receptors and/or CheA. Several biochemical studies have indicated the dependence of the sensory complex stability on the adaptive modification state of receptors and/or on temperature, which may potentially allow environment-dependent tuning of its signalling properties. However, the extent of such regulation in vivo and its significance for chemotaxis remained unclear.